Correlation Between Understanding Body Movement Systems and Habits of Maintaining Bone Health in Elementary School Students - Lili Kasmini (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the correlation between elementary school level students' understanding of the concept of movement systems in humans and their habits in maintaining bone health. Because maintaining bone health is something that must be paid attention to, especially in children at their growing age. Habits of maintaining bone health must be supported by elementary school level students' knowledge regarding the process of growth and development in the human body. This research uses a correlation analysis method, with the Product Moment correlation technique. The number of samples used in this research was 35 class VI students from 5 elementary schools in Banda Aceh City. The instruments used are test questions related to the movement system material in the chapter on how our bodies move, and also a student response questionnaire regarding their daily habits in maintaining bone health. The research results can be concluded that the correlation obtained through the Product Moment correlation test can determine the relationship between the two variables at 0.64 with strong criteria. So there is a strong correlation between the first variable, namely the level of understanding of students' concepts regarding how the body moves and the second variable, namely their habits of maintaining healthy bones. The results of the correlation coefficient obtained show changes in students' habits as they understand the concepts they gain.